2004
DOI: 10.1093/her/cyg051
|View full text |Cite
|
Sign up to set email alerts
|

The Stages of Change in three stage concepts and two modes of physical activity: a comparison of stage distributions and practical implications

Abstract: Stages of Change were assessed for three stage definitions and two modes of health-enhancing physical activity (HEPA) in a representative telephone survey in Switzerland (participation 55.8%; n = 1471). Two five-stage definitions focusing either on intention to change or current behavior were integrated into a seven-stage concept, taking into account both aspects. The two target behaviors were activities with at least moderate intensity and activities with vigorous intensity. According to the two five-stage de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, the significant positive relationship found between the stages of change in physical activity and strenuous physical activity in leisure and commute time in the main study (Lorentzen et al, submitted) lends support for the use of the stages of change construct as an outcome measure. Finally, the lack of a precise definition of regular physical activity may have reduced the reliability and validity of the stages of change measure, as Martin-Diener and colleagues [48] found that an individual can be in different stages of change depending on the definition of the behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant positive relationship found between the stages of change in physical activity and strenuous physical activity in leisure and commute time in the main study (Lorentzen et al, submitted) lends support for the use of the stages of change construct as an outcome measure. Finally, the lack of a precise definition of regular physical activity may have reduced the reliability and validity of the stages of change measure, as Martin-Diener and colleagues [48] found that an individual can be in different stages of change depending on the definition of the behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This was adjusted in a revised version of the instrument for the project "Zurich GPs' exercise counselling sessions for the over-65s" (Märki et al in press), in that Preparation was subdivided into three differentiated algorithms. A similar division was undertaken by Martin-Diener et al (2004). Effectiveness analyses were based on stage change, and time spent in regular lifestyle moderate-intensity activities or sport of at least moderate intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The first module offers a maximum of four tailored feedbacks using questionnaires on stages of change, decisional balance, processes of change, and self-efficacy. Stages of change are assessed according to a seven-stage concept focusing on current behavior (moderate- and vigorous-intensity activity) as well as on intention to change [34]. The decisional balance and self-efficacy scales are based on instruments of Basler et al [35], and the processes of change scale on instruments of Marcus et al [36], and Nigg and Riebe [37].…”
Section: Methodsmentioning
confidence: 99%
“…Depending on their current stage of change, visitors are guided trough one, three, or four sections of the module. More information is available in Martin-Diener et al [34]. The module on strength and flexibility training offers a maximum of two tailored feedbacks based on questionnaires assessing five stages of change as well as attitudes and knowledge regarding strength training.…”
Section: Methodsmentioning
confidence: 99%